Khazanah: Cornelis van Vollenhoven - Latipulhayat, Atip (Faculty of Law, Padjadjaran University, 2017)
âWhat is needed, is this: practical implementation, along eastern lines, of eastern thoughts and the eastern approach of adat-law to the modernâ¦needs ofâ¦ the contemporary [Netherlands] Indiesâ¦ Adat-law alone, which satisfies eastern needs and speaks to eastern hearts, can be said to parallel the short-sighted recklessness of western law, if only its discovery, effects, insemination can be furthered in the eastern mindâand who can better do this than the Indonesians?â Cornelis van Vollenhoven, 1928